Comparison of MR Imaging with PET and IctalSPECT in 118 Patients with Intractable Epilepsy - Won, Hyung Jin; Chang, Kee-Hyun; Cheon, Jung-Eun; Kim, Hong Dae; Lee, Dong Soo; Han, Moon Hee; Kim, In-One; Lee, Sang Kun; Chung, Chun-Kee (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: MR imaging, PET, and ictal SPECT have been studied extensively as individual techniques in the localization of epileptogenic foci, but only a few comparative studies have been done. We evaluated the concordance rates of ictal video/EEG, MR imaging, PET, and ictal SPECT to compare the sensitivities of these imaging methods in the lateralization of epileptogenic foci.METHODS: The study included 118 consecutive patients who underwent surgery for medically intractable epilepsy and who were followed up for 12 months or more. MR imaging was compared retrospectively with ictal video/EEG, FDG-PET, ictal 99mTc-HMPAO SPECT, and invasive EEG as to their ability to localize the epileptogenic focus; the pathologic findings served as the standard of reference.RESULTS: MR imaging was concordant with video/EEG, PET, and ictal SPECT in 58%, 68%, and 58% of patients, respectively. With the pathologic diagnosis as the standard of reference, MR imaging, PET, and ictal SPECT correctly lateralized the lesion in 72%, 85%, and 73% of patients, respectively. Of the patients with good outcomes, MR imaging, PET, and ictal SPECT were correct in 77%, 86%, and 78%, respectively. In the good outcome group, MR imaging was concordant with PET and ictal SPECT in 73% and 62% of patients, respectively. Of 45 patients who underwent invasive EEG, MR imaging was concordant with the invasive study in 47%; PET in 58%; and ictal SPECT in 56%. Of 26 patients with normal MR findings, PET and ictal SPECT correctly lateralized the lesion in 80% and 55%, respectively.CONCLUSION: Overall concordance among the techniques is approximately two thirds or less in lateralizing epileptogenic foci. PET is the most sensitive, even though it provides a broad approximate nature of the epileptogenic zone, which is not adequate for precise surgical localization of epilepsy. PET and/or ictal SPECT may be used as complementary tools in cases of inconclusive lateralization with ictal video/EEG and MR imaging.